Environmental Awareness: A Phenomenological Study of Al-Faruq and Bahrul Hidayah Islamic Boarding Schools in Bandung - Komarudin, Didin; Anwar, Saeful (International Journal of Nusantara Islam, 2024)
Environmental issues have become an integral part of Muslim life. When Islam looks at ecological issues, environmental ideas emerge based on a form of constructive theology with a focus on the relationship between humans, nature and God. Religious doctrine has shown great concern for the environment. Humans, in their relationship with God, also relate to nature as fellow creatures of God. In dealing with God, humans need nature as a means to know and understand God. Pesantren as an Islamic educational institution cannot be separated from environmental issues. Based on the researcher's observation, it was found that in the pesantren environment there was still a lack of awareness in managing the environment. This research uses a descriptive-qualitative method with a religious phenomenology approach in analysing the awareness of environmental theology in Al-Faaruuq salafi pesantren and Bahrul Hidayah Cicalengka pesantren. The stages in this research are; orientation, exploration, and member check. The data sources taken are purposive sampling, namely figures who are considered important such as kiai/ustaz, santri, environmental activists, and the surrounding community. While the data collection process is done through observation, in-depth interviews, documentation. The findings in the first study, humans as God's representatives (khalifah), therefore humans must preserve nature. Because nature is His entrustment. Second, God must be used as the centre of the cosmos. In this case, it is the centre of teaching (tawhid), all human actions must go to God. Third, in Pesantren Al-Faaruuq and Pesantren Bahrul Hidayah, preserving the environment is obligatory, because it aims for the safety, welfare and sustainability of humans, even for the implementation of prayer rituals requires water to wash (wudu) and put nature as a theophany